(untitled) (Journal of Economic Research & Business Administration, 2015)
The article discusses various approaches to the defi nition of «Project Management», as well as the origin of the phenomenon of project. It considers development and establishment of project management as a branch of science. It reviews this area ofknowledge on a global scale, as well as shows the situation in neighboring countries and Kazakhstan. The analysis of the weaknesses of project management development in Kazakhstan is made. The article also shows the reasons for the development of this area of scientifi c knowledge in Kazakhstan. The article presents statistics based on data from Project Management Institute in the U.S., showing the effectiveness of project management. Based on research of the success of projects, the analysis of the reasons for reducing the effectiveness or failure of projects is produced. At the end of the article the solutions to strengthen the position of project management in our country are given.